Material flow analysis in indentation process by 3D Digital Image Correlation - Bermudo-Gamboa, Carolina; Martin-Bejar, Sergio; Trujillo-Vilches, Francisco Javier; Castillo-López, Germán; Sevilla-Hurtado, Lorenzo (UNED, 2019)
Focusing in the application of the 3D Digital Image Correlation technique, this work proposes a material flow analysis in an indentation process. The study establishes the methodology for the calibration and implementation of the 3D image sensing technology for deformation measurements. The purpose is to continue with the validation of the DIC application to the indentation processes, where a deep penetration is achieved and extensive material flow is produced. With the 3D DIC technique is possible to perform accurate deformation measurements in not planar specimens and study the material emerging towards the exterior of the tested specimen, which is not possible with the 2D DIC technique. Although previous 2D studies were efficient detecting the flow field and von Mises strains on the specimens tested, the bulge emerging under the punch on the front surface (dead zone) could not be studied due to its predominantly 3D character. Therefore, present work implements a 3D methodology that carries out a complete study of the deformation, including the material flow that occurs on the Z axis, towards the exterior of the tested specimen, optimizing previous analyses.
Keywords: Digital Image Correlation; experimental methodology; incremental forming; plastic deformation